Education and Globalistics - Arkady Ursul; Tatiana Ursul (International Society of Philosophy and Cosmology, 2017)
It is shown that the study of global processes and globalization is already taking effect on the prospects of global transformation of education, which can not only find their planetary community and integrity, but also a tendency to fill its subject field with global content. It is noted that education should be not only upgraded, but also futurized, in certain aspects, to become a leading education, effectively paving the way to a desired global sustainable future. It is assumed that the formation and evolution of models and types of global education will be run by a new type of global research - education and globalization as an interdisciplinary field that connects global studies and the science of education. Among the common and the most important global processes in education, which will study the educational globalistics, processes such as globalization of education and the formation of global education and the patterns of their evolution.